2018
DOI: 10.1136/archdischild-2017-314608
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity associated with depression in children? Systematic review and meta-analysis

Abstract: Childhood mental illness is poorly recognised by healthcare providers and parents, despite half of all lifetime cases of diagnosable mental illness beginning by the age of 14 years. Globally, depression is the leading cause of disease burden, as measured by disability-adjusted life years, in children aged 10-19 years. Untreated, it is associated with poor school performance and social functioning, substance misuse, recurring depression in adulthood and increased suicide risk, which is the second leading cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
133
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 44 publications
(12 reference statements)
8
133
3
6
Order By: Relevance
“…In the United States, 8.9% specifically have obesity . Overweight and obesity in childhood increase the risk for numerous physical and psychosocial problems during childhood, , including non‐alcoholic fatty liver disease, type 2 diabetes, and depression . Additionally, excess weight gain during the preschool years may specifically impact lifelong health: Children with overweight by the age of 5 years face a four to five times increased risk of having overweight as adolescents and an increased risk of having obesity as adults .…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, 8.9% specifically have obesity . Overweight and obesity in childhood increase the risk for numerous physical and psychosocial problems during childhood, , including non‐alcoholic fatty liver disease, type 2 diabetes, and depression . Additionally, excess weight gain during the preschool years may specifically impact lifelong health: Children with overweight by the age of 5 years face a four to five times increased risk of having overweight as adolescents and an increased risk of having obesity as adults .…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that obese children tend to develop not only future lifestyle-related diseases, such as cardiovascular, metabolic and kidney diseases (Costa-Correia et al 2018), but also present childhood diseases, such as asthma (Lang et al 2018). Further, studies have reported the existence of a strong association between obesity and persistent high risk for depression in female children (Sutaria et al 2019). Thus, childhood overweight or obesity is one of the many possible triggers for the onset of various modern lifestyle-related diseases, with this relationship being greater than previously expected (GBD 2015 Obesity Collaborators 2017).…”
Section: Discussionmentioning
confidence: 99%
“…11 Another strong evidence revealed that female children with obesity have significantly higher probabilities of depression as compared with normal-weight female children until adulthood. 12 By contrast, another review concluded that a higher BMI is not associated with depressive symptoms in early adolescence. 13…”
Section: Introductionmentioning
confidence: 98%